Pengaruh Rasio Keuangan dan Pertumbuhan Perusahaan Terhadap Peringkat Obligasi Syariah - Fitriani, Pradini Rifki; Andriyanto, Irsad; Ridwan, Murtadho (AKTSAR: Jurnal Akuntansi Syariah, 2020)
The purpose of this research is to test the influence of profitability, solvability, liquidity, and growth to the Sharia bond’s rating which are listed in the Indonesia Stock Exchange and rated by PT Pefindo. The population of this research is non-financial companies that are listed in Indonesia Stock Exchange. The sampling of this research selected by purposive sampling. The method is a quantitative method. The data analysis technique is ordinal logistic regression using SPSS 23. The result shows that the profitability ratio has a significant positive influence on the rate of Sharia bond’s rating and liquidity ratio has a significant negative influence. While solvability and growth ratio don’t have any influence on the Sharia bond rating.